Interactions between agrochemicals and parasites endangering insect populations - Davide Frizzera; Verena Strobl; Orlando Yañez; Elisa Seffin; Virginia Zanni; Desiderato Annoscia; Peter Neumann; Francesco Nazzi (Environment International)
There is clear evidence for declines of wild insects and high losses of managed ones, thereby threatening their key ecosystem services. Interactions among stressors such as agricultural intensification and invasive species have been implicated in these declines. However, both the nature of these interactions as well as the actual outcomes are often poorly understood. This holds true for ubiquitous agrochemicals and ectoparasitic Varroa destructor mites, and losses of managed honey bee, Apis mellifera, colonies. Here, we show that two pesticides (sulfoxaflor and coumaphos) can enhance parasite reproduction, thereby contributing to host colony losses. A gene expression study revealed a consistent effect on key genes in the hormonal pathways regulating honey bee development, thereby suggesting a link with parasite reproduction. Because all animals have parasites and are exposed to such agrochemicals even in nature reserves, this mechanism could be relevant for a wide range of insect species and may represent a serious threat for their conservation.